CERTAIN TYPES OF DERIVATIONS IN RINGS: A SURVEY - Ali, Shakir; Rafiquee, Naira Noor; Varshney, Vaishali (Journal of the Indonesian Mathematical Society, 2024)
In this overview article, we provide a historical account on derivations, Jordan derivations, (α, β)-derivations, left derivations, pre-derivations, homoderivations, nilpotent derivations, and other variants, drawing from the contributions of multiple researchers. Additionally, we delve into recent findings and suggest potential avenues for future investigation in this area. Furthermore, we offer pertinent examples to illustrate that the assumptions underlying various results are indeed necessary and not redundant.